Education, Racial Identity, and Perceptions of Immigration and Law Enforcement in the United States - Jude Chukwuebuka Ugwuoke (Information Technology and Science (ITScience), 2025)
This research investigates the relationship between education, racial identity, political ideology, and socioeconomic factors in shaping American immigrants' attitudes toward immigration policies and perceptions of law enforcement. Analyzing data from the 2020 American National Election Studies (ANES) survey through multiple linear regression models, the study reveals significant influences of perceived police brutality and racial bias on public trust in law enforcement, with political ideology being a notable determinant in forming opinions on both immigration and policing. The findings emphasize the adverse impact of aggressive policing and racial profiling on immigrants' trust in law enforcement, highlighting the linkage between education and race in modulating perceptions of immigration policies. The results illustrate several ways sociodemographic factors influence views on these pivotal issues and underscore the critical need for policy approaches that are mindful of the diversity of experiences and attitudes within immigrant communities. By unraveling the layered influences on immigrants' perceptions of immigration and policing, this research contributes valuable insights towards developing more informed, inclusive, and empathetic policy frameworks, reflecting the complex nature of immigration and law enforcement issues in a multifaceted societal context.